Lending without creditor rights, collateral, or reputation: The "trusted assistant" loan in 19th century China - Meng Miao; Niu Guanjie; Thomas Noe (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
This paper considers lending to finance projects in a setting where repayment enforcement appears impossible. The loan was illegal and thus legally unenforceable. Creditors were incapable of applying private coercion to force repayment. Borrowers lacked both collateral and reputation capital. Project cash flows were unobservable. The projects were the acquisition of Imperial administrative posts by scholars in nineteenth century Qing China. The lending mechanism was the "trusted-assistant loan." Our model of trusted-assistant lending shows that it is a renegotiation-proof implementation of efficient state dependent financing. Empirical analysis of officials' diaries and bank records shows that the employment of trusted-assistant lending and the performance of trusted-assistant loans conforms roughly with the model's predictions.
URN:NBN:fi:bof-201709011587
Keywords: N25; G21; D86; 330